Reduction Design of IPMSM Torque Ripple using Design of Experimental - et.al, Do-hyun Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the internal permanent magnet synchronous motor (IPMSM), torque pulsation occurs under no load. This is called cogging torque, and this causes noise and vibration during startup. Use factorial design, one of the experimental designs (DoE), to find the level of the factor with the lowest cogging torque and harmonic distortion (THD). The level of the found factor is applied to the analysis model. The main factors in factorial design are the skew step and skew angle. Based on the optimal factor level found through factor design, we compared the waveforms of torque ripple and line voltage at the maximum speed and the base speed of the analysis model and the model to which the skew was applied through finite element analysis (FEM). As the skew was applied, the harmonics were reduced, thereby reducing the torque ripple, and the line voltage waveform was also applied to the skew, resulting in a smoother waveform.